The association between interpregnancy intervals and preterm birth: a systematic review and meta-analysis - Wen, Xueheng; Liang, Weilun; Zhai, Jinguo; Wang, Yunxia; Zheng, Pingping; Wang, Shiying (BMC pregnancy and childbirth, 2025)
Research has shown a relationship between interpregnancy intervals (IPIs) and preterm birth, but a comprehensive understanding remains elusive. The aim of this systematic review and meta-analysis was to examine the effect of different IPIs on the risk of preterm birth METHODS: Systematic searches were conducted in PubMed, Cochrane, Web of Science, and Embase up to June 2, 2023. Studies included in the review provided data on IPIs and preterm birth outcomes, assessed via the NOS quality scale. A Bayesian network meta-analysis was performed to evaluate the association between IPIs and preterm birth. From 34 studies and 8,646,679 individuals, the optimal IPIs were found to be 24-29 months, showing significantly lower risks of preterm birth at less than 32 weeks of gestation [OR=0.55 (95%CI: 0.50 - 0.62)]and at less than 37 weeks of gestation[OR=0.61 (95%CI: 0.59 - 0.63)]compared to IPIs less than 5 months. IPIs of 24-29 months significantly reduce the risk of preterm birth, suggesting a potential target range for family planning and clinical recommendations. Not applicable.